2015
DOI: 10.1260/1747-9541.10.5.911
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Performance of Scoring Manoeuvres and Lower-Body Strength and Power in Elite Surfers

Abstract: The purpose of this study was to determine whether any significant associations were present between lower-body strength and power, and the performance of turning and aerial manoeuvres in elite surfing athletes. Eighteen competitive male surfers performed a battery of physical tests (countermovement jump (CMJ), squat jump (SJ), and isometric mid-thigh pull (IMTP)) during a single session, in addition to having their performance of turning and aerial manoeuvres ranked from highest to lowest. Significant associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 14 publications
(19 reference statements)
4
49
2
Order By: Relevance
“…Importantly, PF has been shown to be highly reliable within and between sessions [ 8 , 11 , 14 , 15 , 16 ] and may offer a surrogate to 1RM testing due to its strong associations with 1RM back squat [ 2 , 12 , 17 , 18 , 19 ], PC [ 17 , 18 , 20 ], deadlift [ 9 ], and weightlifting performance [ 13 , 21 , 22 ]. Furthermore, strong associations have been observed between absolute or relative PF with dynamic performance such as vertical jump (VJ) height [ 19 , 23 , 24 , 25 , 26 , 27 , 28 ], drop jump reactive strength index [ 29 ], sprint time [ 3 , 25 , 30 ], change of direction speed time [ 2 , 3 , 31 , 32 ], sprint cycling performance [ 23 ], and throwing distance [ 33 , 34 ]. Collectively, these findings rationalize the assessment of PF through IMTP testing and highlight the importance of PF to dynamic athletic performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, PF has been shown to be highly reliable within and between sessions [ 8 , 11 , 14 , 15 , 16 ] and may offer a surrogate to 1RM testing due to its strong associations with 1RM back squat [ 2 , 12 , 17 , 18 , 19 ], PC [ 17 , 18 , 20 ], deadlift [ 9 ], and weightlifting performance [ 13 , 21 , 22 ]. Furthermore, strong associations have been observed between absolute or relative PF with dynamic performance such as vertical jump (VJ) height [ 19 , 23 , 24 , 25 , 26 , 27 , 28 ], drop jump reactive strength index [ 29 ], sprint time [ 3 , 25 , 30 ], change of direction speed time [ 2 , 3 , 31 , 32 ], sprint cycling performance [ 23 ], and throwing distance [ 33 , 34 ]. Collectively, these findings rationalize the assessment of PF through IMTP testing and highlight the importance of PF to dynamic athletic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest to sports scientists and strength and conditioning coaches is the relationship between isometric force-time characteristics and countermovement jump (CMJ) height, CMJ peak power (PP), and CMJ peak RFD, in order to strengthen the rationale for strength diagnostic profiling of athletes through the IMTP. Numerous studies have shown a positive relationship between IMTP absolute PF and CMJ height [ 19 , 20 , 23 , 24 , 27 ], IMTP relative PF and CMJ height [ 25 , 26 , 28 ], IMTP absolute PF and CMJ PP [ 20 , 21 , 23 , 27 ], and IMTP absolute PF with CMJ peak RFD [ 27 ]. In addition, positive associations have been observed between IMTP time-specific force values and CMJ height [ 25 , 26 ] and CMJ PP [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such analysis, of both recreational and competitive surfing suggests that surfing can be characterized as a sport requiring multiple short duration and high-intensity bouts of all-out paddling intercalated with relative short paddling (O. . Thus, both technical and physical proficiency are required to succeed in surfing (Fernandez-Gamboa, Yanci, Granados, & Camara, 2017;Secomb, Farley, et al, 2015). Performance analysis incorporates several applications including tactical and technical evaluation, analysis of movement and physical demands (Axel, Crussemeyer, Dean, & Young, 2018;O.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, incorporating an appropriate resistance training program under qualified supervisions may be advantagous for reducing the likelihood of sports related injuries [8,10]. Furthermore, greater physical qualities [e.g., strength and power] have been reported to associate with surfing performance [28,30]. Recent evidence revealed physical performance reflected selection from a group of elite junior surfers to represent Surfing Australia National Junior Team at the International Surfing Association World Junior Surfing Championship [33].…”
Section: Introductionmentioning
confidence: 99%